Television viewing and hostile personality trait increase the risk of injuries. Issue 1 (2nd January 2017) - Fabio, Anthony; Chen, Chung-Yu; Dearwater, Steven; Jacobs, David R.; Erickson, Darin; Matthews, Karen A.; Iribarren, Carlos; Sidney, Stephen; Pereira, Mark A.
Abstract : Individuals with high levels of hostility may be more susceptible to the influence of television on violence and risk taking behaviors. This study aimed to examine whether hostile personality trait modifies the association between TV viewing and injuries. It is a prospective study of 4, 196 black and white adults aged 23 to 35 in 1990/1. Cross-lagged panel models were analyzed at three 5-year time periods to test whether TV viewing predicted injuries. Covariates were gender, race, and education. Individuals who watched more TV (0 hours, 1–3 hours, 4–6 hours, and ≥7 hours) were more likely to have a hospitalization for an injury in the following 5 years across each of the three follow-up periods [OR = 1.5 (95%CI = 1.2, 1.9), 1.5 (1.1, 1.9), and 1.9 (1.3, 2.6)]. The cross-lagged effects of TV viewing to injury were significant in the high hostility group [OR = 1.4 (95%CI = 1.1, 1.8), 1.3 (1.0, 1.8), and 2.0 (1.3, 2.9)] but not in the low hostility group [OR = 1.3 (95%CI = 0.6, 2.2), 1.1 (0.6, 2.1), and 1.4 (0.7, 2.8)]. Additionally, a statistically significant difference between the two models (P < 0.001) suggested that hostility moderated the relationship between TV watching and injury. These findings suggest that individuals who watch more TV and have a hostile personality trait may be at a greater risk for injury.